Methods of obtaining nickel molybdates and composites of molybdate/carbon material for electrodes of hybrid supercapacitors (Review) - Popovych, O.M.; Budzulyak, I.M.; Kotsyubynsky, V.O.; Popovych, O.V.; Rachiy, B.I.; Ilnytskyi, R.V.; Yablon, L.S. (Physics and Chemistry of Solid State, 2020)
Nickel molybdate due to its electronic configuration, stable crystalline framework, oxidation-reduction behavior displays perfect physical and chemical properties and rather high electrical conductivity that altogether lets the material display high total capacity. The research work classified modern methods of obtaining nickel molybdates and composites with carbon material on their basis. We have analyzed the fundamental stages of hydrothermal, microwave synthesis, ultrasonic dispersion, mechano-chemical, sol-gel method, and chemical precipitation method. The influence of different synthesis conditions on phase structure, morphology, physical and electrochemical properties of material was displayed.